Rola Iranu, Iraku i Syrii w polityce białoruskiej (Politeja, 2018)
The Role of Iran, Iraq and Syria in the Policy of the BelarusianRelations between Belarus and Iran, Iraq and Syria after 1998 took on the nature of political alliance. The factor connecting Belarus with these countries was their isolation by the West because of the policy of internal or foreign. Sanctions or restrictions imposed on these countries on the initiative or with the participation of the United States created an additional platform for Minsk agreements with Tehran, Baghdad and Damascus. Anti‑Americanism four countries has become a common feature of their foreign policy and defense cooperation. Closeness of political relations was accompanied by a desire to establish a broad economic cooperation between the four countries. At the beginning of 21st century it grew by leaps and bounds each year, the volume of trade between Belarus and Iran, Iraq and Syria. Level exchanges with Iran and Syria, however, quickly reached a level corresponding to the potential capabilities of the parties and far removed from the expectations of leaders. Any dealings with Iraq were interrupted as a result of the occupation of that country by the United States and the coalition.